Deferasirox-loaded polymeric micelles as nanoformulated iron chelating chemotherapy of prostate cancer - Punlop Chalermpanapun (2018)
© 2015 IEEE. Nowadays, conventional chemotherapy is commonly used in many cancers and support for other cancer therapies to improve the success rate of treatment. However, the conventional chemotherapy has many severe side effects. Thus, polymers and nanotechnology are applied to develop drug delivery systems and to increase the properties of anti-cancer drug including reduction of side effect. Many reports show that the cancer cells express higher iron level therefore inhibiting iron metabolism in cancer cells is a novel strategy to treat cancer. Generally, iron chelator used to reduce iron overload in the thalassemia patients. In this experiment, iron chelator, deferasirox (Dei) was used as anticancer drug that is trapped iron in cancer cells leading to antiproliferation of cancer cells. Deferasirox was loaded into PEG-A-PCL (MW of PEG = 5.0 kDa, MW of PCL = 5.0 kDa) polymeric micelles by the solvent evaporation method. The hydrodynamic diameter of Def-loaded micelles was measured. Released studies of Def were monitored in PBS pH 7.4. The drug loading content (DLC) and drug loading efficiency (EE) were determined. Def-loaded micelles was incubated with PC-3 cells for 72 h and viability of PC-3 was determined by MTT assay. The result shows that ICS0of free Def was 8.74 μM and IC50of Def-loaded Micelles was 12.85 μM. This suggests that the Def and Def-loaded micelles were able to trap a free iron in cytoplasm and induce antiproliferation of PC-3 cells that is an alternative technique to kill cancer cells.